MANUFACTURING AND TESTING HIGH VOLTAGE FILTER CAPACITORS - ISTÓK RÓBERT; GÁL TIBOR; JASZTRAB PÉTER JÁNOS; PETRU GABRIEL PUIU; SZÉN ISTVÁN (Journal of Engineering Studies and Research)
This paper presents the manufacturing and testing methods of 30kV and 33nF high voltage filter capacitors. One of the biggest advantages of small companies is that they are able to produce a high diversity of capacitors in small quantities. One of the prices of this flexibility is a higher level of manual manufacturing process in production. But this higher level of manual manufacturing does not mean lower quality in the final product. For high quality products in the high voltage industry, it is necessary to do routine tests in all of the products. For high voltage capacitors the following three tests must be done to ensure quality: voltage strength test, partial discharge test, capacitance and dissipation factor test. The capacitance and dissipation factor test have to be done at different voltage levels. The voltage strength test has to be done at least 20% higher than the rated voltage. This kind of test gives us information not only about the quality of the product itself, but about distribution of the capacitance for example, or about the strength of the production process, and about the quality management system of the company.